The contribution of teamwork, thinking styles, and innovation towards knowledge management - Ratnasingam, Malini (Universiti Utara Malaysia Press, 2009)
Knowledge management can be enhanced by creating conditions that facilitate knowledge creation, thus the concepts of teamwork,thinking styles, and innovation are central to the effective utilisationof knowledge. This paper presents the results of a survey of 156 civil servants at Putrajaya, investigating relationships between teamwork and thinking styles with technology diffusion and innovation and organisational innovation. The results indicated that team quality and external thinking style made the greatest contribution toward technology diffusion and innovation.